(untitled) (Studia Prawnicze / The Legal Studies, 2012)
Zasada sprawiedliwości wyrównawczej obliguje do wynagrodzenia szkód doznanych wskutek orzeczenia i wykonania sankcji karnych całkowicie bezzasadnych lub ustalonych na zbyt wysokim poziomie. Państwowy wymiar sprawiedliwości, reagując prawidłowo na popełnienie przestępstwa, powinien zastosować wobec podmiotu naruszającego istniejący porządek sankcje statuowane przepisami prawa. Błędy popełnione przy dystrybucji kar są sprzeczne z zasadą sprawiedliwości, nakazującą zapłatę za spowodowane dobro lub dokonanie odpowiedniej odpłaty w zamian za wyrządzone zło. Dla przywrócenia stanu równowagi naruszonej wyrządzeniem bezprawnej szkody konieczne są kompleksowe działania wynagradzające. Inauguruje je prawidłowe rozstrzygnięcie kwestii winy i kary osoby prawomocnie osądzonej lub pozbawionej wolności w ramach środków przymusu, wydane w ramach nadzwyczajnych środków odwoławczych. Drugą odsłonę batalii o przywrócenie naruszonego porządku stanowi zasądzenie rekompensat pokrywających uszczerbek spowodowany niesprawiedliwym zastosowaniem represji karnych. In case of the death of a person injured by faulty operation of prosecution and jurisdictional authorities, the right to enforce claims for damages is acquired by persons legally or actually related to the deceased - also his or her children. In the event of death of the directly injured the entitled persons acquire independent rights to damages (persons receiving alimony from an accused person) or as the result of the so-called singular succession they acquire the right to enforce the claim of the deceased (relatives of 1944 - 1956 repression victims as also in the period of martial law, and perpetrators of offences). The independent rights of children are limited to compensation of own economic losses suffered in the consequence of deprivation of support by imposition of sentence, preventive measures or pre-trial arrest. Successors of claims of the accused or repressed acquire the right to claim for damages and compensation due to the transferor. The legal bond between parents and children is imitated by the relationship of adoption, therefore, the group of persons entitled to enforce claims for damages after death of a directly injured person includes those persons remaining with him or her in the relation of adoption, both through full and partial adoption. The claim of children of the repressed or accused person is divisible. Their potential joint participation in one trial does is not required joint participation. Therefore, each of the claimants may independently execute his or her part of deceased’s provision.